Pemahaman Perangkat Desa Terhadap Aspek Perpajakan dalam Pengelolaan Keuangan Desa di Kabupaten Bantul - Dwi Sudaryati; Sucahyo Heriningsih; Lita Yulita Fitriyani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat UPN Veteran Yogyakarta, 2020)
The Central Government's policy on the transfer of Village Funds continues to increase significantly, this is a potential tax cut and collection. Law No. 6 of 2014 concerning Villages (Village Law) makes the role of village officials, very important to regulate and manage village finances, including the taxation aspects. However, village apparatus do not fully understand and understand aspects of taxation in village financial management. This study aims to determine the understanding of village apparatus on tax aspects in village financial management, which includes tax collection and deduction. This research was conducted in villages in Bantul Regency which had BUMDes in accordance with data from the Ministry of Home Affairs (Prodeskel) of 35 villages. Respondents in this study are village apparatus involved in village financial management, including village heads, village secretaries, and village treasurers. This study uses primary data in the form of questionnaires and interviews. The results showed that village apparatus in Bantul Regency fully understand the implementation of taxation aspects in village financial management.